SOCIAL MEDIA AS A PATHWAY TO NEWS: A CASE STUDY ON MALAY YOUNG ADULTS’ PERCEPTION - Mohd Shah, Nurul Nisha; Amairudin, Muhammad Firdaus; Asan, Amira; Basinon, Mohd Radzman; Wan Lokman, Tun Mastura (Jurnal ’Ulwan, 2023)
This qualitative study focuses on the capabilities of social media in framing issues as perceived by Malay young adults. This study is being addressed through two research objectives, which are to identify the categories of issues that always being framed by social media and to determine methods for the issues being framed by social media. The data for the entire research were obtained through in-depth interviews which were conducted to six informants. These informants were selected on the basis of typical sampling, a subset of the purposive sampling with the traits of a social media user, have at least one social media account regardless of language, access to the social media account frequently, technology literate, aged between 15 to 40 years old, Malay race, regardless of gender, social-economic status and education background. The data were analyzed by utilizing thematic analysis by deriving themes from the in-depth interviews. The findings of the research were categorized into two sections. First of all, the issues that always being framed by social media are serious issues which mean they can give impact to the society and the government; and secondly, the researcher concluded that the issues framed in the social media are based on social media users’ preferences. The researcher hoped that this research can help people to deeply understand the agenda setting theory in which how issues that are framed by social media might influence people by creating a public agenda. Social media can be a powerful source as the issues framed by it is covered frequently and prominently readers will regard the issue as more important.